2018
DOI: 10.1007/s00203-018-1501-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid molecular identification and differentiation of common Salmonella serovars isolated from poultry, domestic animals and foodstuff using multiplex PCR assay

Abstract: Salmonella is widely distributed throughout the world and can be found in poultry industry, animal breeding centers, food and feedstuffs of all geographical regions. This study was conducted to determine and identify Salmonella serovars isolated from poultry, calves and foodstuffs (poultry and animals products such as egg and meat). A total of one hundred isolates of Salmonella serovars including Salmonella Typhimurium, Salmonella Enteritidis, Salmonella Infantis, Salmonella Gallinarum and Salmonella Pullorum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…After 16 h incubation at 37 °C, 0.1 mL and 10 mL of BPW were transferred into 10 mL of tetrathionate broth and 100 mL of selenite broth, respectively. Subcultures were spread on xylose-lysine-deoxycholate (XLD; Land Bridge, China) agar, xylose-lysine-tergitol 4 (XLT4; Land Bridge, China) agar, and Hektoen (HE; Hopebio, China) agar, and incubated at 37 °C for 24 h. The typical Salmonella colonies were confirmed by PCR amplification of the hut gene, and the primers were as follows, hut-F, 5′-ATGTTGTCCTGCCCCTGGTAAGAGA-3′, hut-R, 5′-ACTGGCGTTATCCCTTTCTCTGCTG-3′ [ 37 ]. Serotypes were determined by a slide agglutination test with O-antigen antiserum and a tube agglutination test with H-antigen antiserum, and confirmed by quadruplex PCR analysis as previously reported [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…After 16 h incubation at 37 °C, 0.1 mL and 10 mL of BPW were transferred into 10 mL of tetrathionate broth and 100 mL of selenite broth, respectively. Subcultures were spread on xylose-lysine-deoxycholate (XLD; Land Bridge, China) agar, xylose-lysine-tergitol 4 (XLT4; Land Bridge, China) agar, and Hektoen (HE; Hopebio, China) agar, and incubated at 37 °C for 24 h. The typical Salmonella colonies were confirmed by PCR amplification of the hut gene, and the primers were as follows, hut-F, 5′-ATGTTGTCCTGCCCCTGGTAAGAGA-3′, hut-R, 5′-ACTGGCGTTATCCCTTTCTCTGCTG-3′ [ 37 ]. Serotypes were determined by a slide agglutination test with O-antigen antiserum and a tube agglutination test with H-antigen antiserum, and confirmed by quadruplex PCR analysis as previously reported [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Swabs were cultured in 9 mL of Gram negative (GN) broth (Tianhe, China) at 37 °C for 24 h before aliquots of 100 mL of the broth were streaked onto Triple Sugar Iron agar (TSI, Oxoid, England). Typical Salmonella colonies were confirmed by PCR amplification of the hut gene, the primers were as followed, hut-F, 5’-ATGTTGTCCTGCCCCTGGTAAGAGA-3′, and hut-R, 5’-ACTGGCGTTATCCCTTTCTCTGCTG-3′ [18]. S .…”
Section: Methodsmentioning
confidence: 99%
“…The genomes of approximately 20 strains of S. bongori have been registered, among which the representative strain is S. bongori NCTC 12419 (NCBI genome ID 1089). The sseL , spvC (Peterson et al , 2010), avrA , stn , stm (Amin et al , 2016), spv , hut , fljB (Alzwghaibi et al , 2018), hilA , fimA and hns (Jeyasekaran et al , 2011) gene regions have been reported as markers for the Salmonella genus. In addition, multiplex PCR analysis based on the fljB , gatD , invA , mdcA , stn and STM4057 genes is used for Salmonella genus identification (Lee et al , 2009).…”
Section: Wgs and Genetic Marker Identification Of Related Microbes Onmentioning
confidence: 99%